2008
DOI: 10.1080/13803390701363803
|View full text |Cite
|
Sign up to set email alerts
|

Time estimation and episodic memory following traumatic brain injury

Abstract: The ability to accurately estimate the passage of time plays an important role in helping to structure daily activities. In this study, we used a prospective verbal time estimation paradigm to investigate time perception in 27 moderate to severe traumatic brain injury (TBI) participants and 27 controls. Verbal time estimations were made for filled intervals both within (i.e., <30 s) and beyond the time frame of working memory. We found that the TBI participants exhibited normal or near-normal estimates of time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
47
3
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(55 citation statements)
references
References 62 publications
4
47
3
1
Order By: Relevance
“…Indeed, in Meyers and Levin's (1992) study, performance at verbal estimation task was not analyzed due to the extreme variability noted in the TBI sample. Schmitter-Edgecombe and Rueda (2008), as well as Anderson and Schmitter-Edgecombe (2011), reported lower accuracy (absolute score), higher under-estimation (RATIO) and more variability (CV) in TBI patients than controls.…”
Section: Time Perception In Traumatic Brain Injury Patientsmentioning
confidence: 95%
See 3 more Smart Citations
“…Indeed, in Meyers and Levin's (1992) study, performance at verbal estimation task was not analyzed due to the extreme variability noted in the TBI sample. Schmitter-Edgecombe and Rueda (2008), as well as Anderson and Schmitter-Edgecombe (2011), reported lower accuracy (absolute score), higher under-estimation (RATIO) and more variability (CV) in TBI patients than controls.…”
Section: Time Perception In Traumatic Brain Injury Patientsmentioning
confidence: 95%
“…In the end, in spite of the importance of adequate temporal abilities in everyday activities, only seven studies investigating time perception following TBI were identified and included in the present work (Meyers and Levin, 1992; Perbal et al, 2003; Schmitter-Edgecombe and Rueda, 2008; Anderson and Schmitter-Edgecombe, 2011; Mioni et al, 2012, 2013a,b). Table 1 provides a summary of the findings reported in these articles.…”
Section: Time Perception In Traumatic Brain Injury Patientsmentioning
confidence: 99%
See 2 more Smart Citations
“…The data was gathered as part of a larger test battery that included standardized neuropsychological tests and other experimental measures (for further review of experimental tasks see [40]). All neuropsychological measures were administered in accordance with standardized instructions and were collected across 2 days of testing.…”
Section: Methodsmentioning
confidence: 99%